2016
DOI: 10.1002/etc.3544
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of single‐walled carbon nanotubes and saxitoxin: Ab initio simulations and biological responses in hippocampal cell line HT‐22

Abstract: Saxitoxins (STXs) are potent neurotoxins that also induce cytotoxicity through the generation of reactive oxygen species. Carbon nanotubes (CNTs) are nanomaterials that can promote a Trojan horse effect, facilitating the entry of toxic molecules to cells when adsorbed to nanomaterials. The interaction of pristine single-walled (SW)CNTs and carboxylated (SWCNT-COOH) nanotubes with STX was evaluated by ab initio simulation and bioassays using the cell line HT-22. Cells (5 × 10 cells/mL) were exposed to SWCNT and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In fact, several studies showed that co-exposure with fullerene C 60 can affect the uptake rate and toxicity of other environmental contaminants (Azvedo Costa et al, 2012;Ferreira et al, 2014). Recently, Ramos et al (2017) of DNA strand breaks were also observed concluding that B(α)P and/or C 60 induce tissue and DNA damage in exposed marine mussels, confirming their function as genotoxicants.…”
Section: "Trojan Horse" Effectsmentioning
confidence: 94%
“…In fact, several studies showed that co-exposure with fullerene C 60 can affect the uptake rate and toxicity of other environmental contaminants (Azvedo Costa et al, 2012;Ferreira et al, 2014). Recently, Ramos et al (2017) of DNA strand breaks were also observed concluding that B(α)P and/or C 60 induce tissue and DNA damage in exposed marine mussels, confirming their function as genotoxicants.…”
Section: "Trojan Horse" Effectsmentioning
confidence: 94%
“…Discovery Studio 2021 software was used to visualize the interaction results and the 2D map of interaction was performed through LigPlot software. The proposed methodology was similarly approached in other studies, such as the interaction in the complex formed by graphene and glutamate [39], and for single-walled carbon nanotubes and human mitochondrial voltage-dependent anion channel [40].…”
Section: Structures Preparation Molecular Docking and Results Analysismentioning
confidence: 99%